Sensorimotor function, balance and dual-task walking speed among stroke survivors with hemiparesis (2022)
Background: Impaired dual-task ability increases the risk of fall and fall-related injuries among stroke survivors. It also limits the extent of community ambulation and overall reintegration into the community after rehabilitation. The aim of this study was to investigate the relationships among sensorimotor function, balance and dual-task walking speed of stroke survivors during a dual-task gait performance among stroke survivors with hemiparesis. Methods: Purposely recruited stroke survivors with hemiparesis who could ambulate independently for at least 10 metres, and who had a score of B20 on the Mini-Mental State Examination participated in this correlational cross- sectional survey. Motor and sensory functions were assessed using the Fugl-Meyer Assessment Scale while balance was assessed using the Berg Balance Scale. Walking speed while ambulating on a 10-meter walkway and button up and down shirts was also assessed. Data were summarized using descriptive statistics and analysed using Pearson's product moment correlation method at Coas Results: Forty-five stroke survivors (35 males) aged 52.5±10.23 years participated in this study. The mean sensory, motor function and balance scores were 10.76± 2.47, 67.09± 19.80 and 47.02 ± 7.24 respectively. There was a significant relationship between motor function and walking speed, as well as between balance and walking speed (p<0.05). Conclusion: Sensory, motor and balance functions are related to dual-task walking speed. Hence, dual-task gait training should be incorporated into the rehabilitation plans for stroke survivors.